Two Children With Steroid-Resistant Significant Proteinuria Due to Nonsense Mutations of the TRIM8 Gene: A Case Report and Literature Review - Li, Xiaojie; Wei, Yaqin; Wang, Meiqiu; Jia, Lili; Shi, Zhuo; Yang, Xiao; Ju, Tao; Kuang, Qianhuining; Xia, Zhengkun; Gao, Chunlin (Frontiers in Pediatrics, 2022)
Background: TRIM8 gene mutations have been reported as the genetic basis of children with autosomal dominant (AD) neuro-renal syndrome, which presents with epileptic encephalopathy, focal segmental glomerulosclerosis (FSGS), developmental delay and mental retardation. Herein we reported on two children with significant proteinuria due to de novo nonsense mutations of the TRIM8 gene. Case presentation: Case 1 was a 7-year-old girl who presented with proteinuria and developmental delay, and her renal biopsy showed FSGS. She developed end-stage renal disease (ESRD) 3 years after onset. Case 2 was another 7-year-old girl who developed proteinuria only at 3 years old, and the renal biopsy showed glomerular segmental mesangial proliferative lesions. The two girls were performed genetic testing but did not find a positive result in the whole exon. However, cluster analysis revealed two new nonsense mutations of TRIM8 gene (c.1461C>A, p.Tyr 487* and c.1453C>T, p.Gln485*). Conclusions: We provide the clinical manifestation of this neuro-renal syndrome for the first time in China. It is necessary to perform genetic testing in children with steroid-resistant significant proteinuria to identify the etiology and avoid the side effects brought on by immunosuppressants.